2020
DOI: 10.1038/s41598-020-63090-9
|View full text |Cite
|
Sign up to set email alerts
|

Qi Dan Li Xin pill improves chronic heart failure by regulating mTOR/p70S6k-mediated autophagy and inhibiting apoptosis

Abstract: Myocardial remodeling represents a key factor in chronic heart failure (CHF) development, and is characterized by chronic death of cardiomyocytes. Cardiac function changes may be attributed to inflammation, apoptosis and autophagy. This study assessed the effects of Qi Dan Li Xin Pill (QD) on heart function, inflammatory factors, autophagy and apoptosis in cardiac remodeling in CHF rats upon myocardial infarction (MI) induction.Male SD rats underwent a sham procedure or left anterior descending coronary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…The beneficial effects of QL on cardiac hypertrophy, ventricular remodeling, and HF through multiple pathways have been widely reported ( Gao et al, 2018 ; Lu et al, 2020 ; Wang et al, 2017 ). Valsartan, an angiotensin II (ANG II) receptor blocker, exerts positive effects in improving chronic inflammation, promoting scar repair, maintaining cardiomyocyte integrity, alleviating ventricular remodeling, and thus preserving cardiac functions ( Shi et al, 2020 ). Further studies indicated that valsartan administration could affect the intestinal microbiota composition and SCFA generation and blunted the LPS-induced elevations of inflammatory cytokines ( Iwashita et al, 2013 ; Qi et al, 2021 ).…”
Section: Disscussionmentioning
confidence: 99%
“…The beneficial effects of QL on cardiac hypertrophy, ventricular remodeling, and HF through multiple pathways have been widely reported ( Gao et al, 2018 ; Lu et al, 2020 ; Wang et al, 2017 ). Valsartan, an angiotensin II (ANG II) receptor blocker, exerts positive effects in improving chronic inflammation, promoting scar repair, maintaining cardiomyocyte integrity, alleviating ventricular remodeling, and thus preserving cardiac functions ( Shi et al, 2020 ). Further studies indicated that valsartan administration could affect the intestinal microbiota composition and SCFA generation and blunted the LPS-induced elevations of inflammatory cytokines ( Iwashita et al, 2013 ; Qi et al, 2021 ).…”
Section: Disscussionmentioning
confidence: 99%
“…mTOR is an important regulatory molecule that induces autophagy, and activating mTOR by phosphatidylinositol 3-kinase (PI3K) and mitogen-activated protein kinase (MARK) transduction can inhibit autophagy. In contrast, the negative regulation of mTOR by adenosine monophosphate-activated protein kinase (AMPK) and p53 signal transduction promotes autophagy (Dong et al, 2019;Shi et al, 2020). The formed mTOR complex is extensively linked to the downstream autophagy-related gene (ATG) family to construct the autophagosomes and ultimately complete the process of ubiquitin-like reactions.…”
Section: Autophagy Pathways In Cardiovascular Diseasesmentioning
confidence: 99%
“…Sciarretta S et al found that in ischemic stress, Rheb, as a GTP-binding protein, could inhibit autophagy by activating mTORC1, thereby aggravating post-ischemic infarct size (Sciarretta et al, 2012). During heart failure and aortic atherosclerosis, miR-212/132, laminar flow and Danqi pills regulated autophagy by modulating autophagyrelated pathways and molecules, affecting cardiac function (Supplementary Table S4) (Oka et al, 2012;Shi et al, 2020;Grootaert et al, 2015;Ucar et al, 2012;Yuan et al, 2020;Wang et al, 2021b). As mentioned before, autophagy restricted to an appropriate extent protects against ischemic injury via maintaining cardiomyocyte homeostasis, degrading organelles, or misfolding proteins that produce adenosine triphosphate (ATP).…”
Section: Autophagy Pathways In Cardiovascular Diseasesmentioning
confidence: 99%
“…Autophagy can promote survival by inhibiting apoptosis under several different conditions, and sometimes lead to cell death by cooperating with apoptosis or as a supplement to apoptosis defects. Tong-Xin-Luo, Tong-Guan Capsules, and Qi-Dan-Li-Xin Pills can all play the role of anti-VR by anti-cardiomyocyte apoptosis and promoting cardiomyocyte autophagy (71)(72)(73). Rapamycin mechanical target is a key regulatory protein involved in protein production, cell growth/proliferation, autophagy, lysosomal function, and the metabolic pathway, and is considered to be the central regulator of cell growth.…”
Section: Apoptosis Factors and Autophagymentioning
confidence: 99%
“…It can also deacetylate p53 to inhibit apoptosis. Qi-Dan-Li-Xin Pill also promotes the autophagy of cardiomyocytes by down-regulating the mTOR/P70/S6K/4EBP1 pathway ( 73 ). Yang-Xin-Kang Tablets, prepared using Panax ginseng C.A.Mey .…”
Section: Molecular Pathways Involved In Cardiac Remodelingmentioning
confidence: 99%